The relationship among somatotype structures, leg volume, leg mass, anaerobic strength and flexibility of elite male athletes in different branches - Marangoz, I.; Bastürk, D. (Journal of Education and Training Studies, 2018)
This study aims to analyze the relationship among somatotype structures, leg volume, leg mass, anaerobic strength and flexibility of elite male athletes in different branches. 90 male athletes who study at School of Physical Education and Sport at University of Kirsehir Ahi Evran and are active in wrestling (n=15), gymnastics (15), football (15), handball (15), volleyball (15) and basketball (n=15) voluntarily participated in this study. Somatotype structures, leg volumes and leg masses of the participants were determined using Heath-Carter, Frustum and Hanavan methods, respectively. Vertical jump test was used to measure anaerobic performance, while sit-and-reach test was used for flexibility performance. Spearman correlation analysis was performed using SPSS 22.0 package program for Windows, and the level of significance was taken as 0.05. As a result, a significant correlation was found between leg volume and mass and anaerobic performance values in football, volleyball, basketball, handball, wrestling and gymnastics, which indicates a decisive role in anaerobic performance. It was observed that athletes with a higher amount of leg volume and mass display a better anaerobic performance. The width of femur circumference and a high amount of muscle mass and fiber in the femur lead to a higher strength in muscles and maximizes the strength.